2014
DOI: 10.1007/s11738-014-1667-9
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide nanoparticle toxicity in mung bean (Vigna radiata L.) seedlings: physiological and molecular level responses of in vitro grown plants

Abstract: In this study, the toxic effect of copper oxide nanoparticles (CuONPs) at the physiological and molecular level was investigated in mung bean (Vigna radiata L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…However, it decreased slightly in 0.05 mgmL −1 CuONPs indicating its toxic nature. According to Nair et al [39] seed germination percentage of Vigna radiata becomes significantly reduced due to toxic effects of CuONPs which was observed in our case also. Furthermore, root length was increased in CuONPs (0.025 mgmL −1 ) treated seedlings compared to control (Table 1).…”
Section: Effects Of Cuonps On Seed Germination and Growthsupporting
confidence: 78%
See 2 more Smart Citations
“…However, it decreased slightly in 0.05 mgmL −1 CuONPs indicating its toxic nature. According to Nair et al [39] seed germination percentage of Vigna radiata becomes significantly reduced due to toxic effects of CuONPs which was observed in our case also. Furthermore, root length was increased in CuONPs (0.025 mgmL −1 ) treated seedlings compared to control (Table 1).…”
Section: Effects Of Cuonps On Seed Germination and Growthsupporting
confidence: 78%
“…Furthermore, root length was increased in CuONPs (0.025 mgmL −1 ) treated seedlings compared to control ( Table 1). Retardation of primary root growth ( Figure 10) was observed upon exposure to higher concentrations of CuONPs (0.05 mgmL −1 ) as it was observed by Nair et al [39].…”
Section: Effects Of Cuonps On Seed Germination and Growthsupporting
confidence: 72%
See 1 more Smart Citation
“…Begum and Fugetsu reported that multi-walled carbon nanotubes (MWCNTs) of 20, 200, 1000, and 2000 mg/L were phytotoxic to red spinach, lettuce, rice, and cucumber, and the shoot and root weights were dramatically decreased with increasing nanotube concentrations [12]. Nair et al showed that the phenotype of mung bean was regulated by media containing copper oxide nanoparticles of 20, 50, 100, 200, and 500 mg/L, and the reactive oxygen species generation in the roots increased gradually with the increase of the nanoparticle concentration [13]. In addition, nanomaterials, such as graphene, CNTs, and copper oxide nanoparticles, have been shown to be cytotoxic to various crops [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These ENPs are also active against natural enemies of the mosquito, suggesting a potential public health problem through disruption of biological control of mosquito populations [64]. There is evidence that CuO-based ENPs are toxic to the reproduction of Enchytraeus crypticus (earthworm) and this may alter soil processes, since earthworms are key players in soil health [75]. Soil processes may also be altered via the nitrogen cycle in plants when impacted by TiO 2 , as well as by Agbased and CuO ENPs.…”
Section: Ecological Effects Of Nps In Soilsmentioning
confidence: 99%